2021
DOI: 10.1016/j.nantod.2021.101161
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and acquired corona of coronavirus in the host: Inspiration from the biomolecular corona of nanoparticles

Abstract: Coronavirus is named for its crown shape. Encoded by the genetic material inherited from the coronavirus itself, this intrinsic well-known “viral corona” can be considered the “inherited corona”. After contact with mucosa or the entrance into the host, bare coronaviruses could become covered by a group of dissolved biomolecules to form one or multiple layers of biomolecules. Different from this inherited corona, the layers acquired from the surrounding environment could be named as “acquired corona”. We highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…[49,83,84] Additionally, the composition of the corona, for example, proteins such as albumin, apolipoprotein E (ApoE), and IgG antibodies, will determine the NMs-cell interactions and cellular uptake mechanisms of liver cells once NMs are distributed in the liver. [85][86][87][88][89][90][91][92][93] Among the different liver cells, most studies are focused on the interactions of NMs with KCs, LSECs, HSCs, and hepatocytes due to their important roles in liver physiology and diseases. The unique liver architecture and location of these liver cells profoundly affect their interaction with NMs and cellular uptake, which will eventually determine the cellular responses (Figure 6).…”
Section: Nms Properties and Cell Type-specific Uptake In The Livermentioning
confidence: 99%
See 1 more Smart Citation
“…[49,83,84] Additionally, the composition of the corona, for example, proteins such as albumin, apolipoprotein E (ApoE), and IgG antibodies, will determine the NMs-cell interactions and cellular uptake mechanisms of liver cells once NMs are distributed in the liver. [85][86][87][88][89][90][91][92][93] Among the different liver cells, most studies are focused on the interactions of NMs with KCs, LSECs, HSCs, and hepatocytes due to their important roles in liver physiology and diseases. The unique liver architecture and location of these liver cells profoundly affect their interaction with NMs and cellular uptake, which will eventually determine the cellular responses (Figure 6).…”
Section: Nms Properties and Cell Type-specific Uptake In The Livermentioning
confidence: 99%
“…[85,86] The structure and composition of the corona are determined by the intrinsic physicochemical properties of NMs, the duration of exposure, and the nature of the physiological environment. [87][88][89] It has shown that the biomolecular corona regulated cellular recognition and penetration of NMs, and further influence their intracellular trafficking. [90,91] Corona proteins have been found to facilitate the binding of the opsonized particle to specific receptor molecules that are available in macrophages.…”
Section: Protein Coronamentioning
confidence: 99%
“…The adsorption of soluble proteins onto synthetic nanoparticles entering the bloodstream has been described to drive their biologic functions (Farshbaf et al, 2022). A similar paradigm has been recently hypothesised to be also valid for the viruses (Gao et al, 2021).…”
Section:  Autoimmune Disordersmentioning
confidence: 94%
“…Therefore, ZnO nanoparticles can act as candidate materials for coating to eradicate the coronavirus due to their novel characteristics [38][39]. Figure (6) displayed the coronavirus structure and its essential components, which included the spike protein, the nucleocapsid protein, the hemagglutinin esterase glycoprotein, the viral genome RNA, the envelope protein, and the membrane protein [ 40]. The present work is built on a hypothetical basis according to published studies [41][42][43][44].…”
Section: Anti-surface Coating For Coronavirusmentioning
confidence: 99%
“…Coronaviruses that have not yet been infected or infected by the host can be covered by a layer of dissolved biomolecules that can be one or more layers thick after coming into contact with mucosa or entering the host [5]. The term "acquired corona" refers to the layers that have been accumulated because of the environment [6]. Coronavirus disease has a range of health conditions and indicators that are distinctive to each individual patient.…”
Section: Introductionmentioning
confidence: 99%